(untitled) (Bulletin KNOB, 2007)
From recent systematic building-historical research in the town of Leiden a frequently applied type of house emerged. This type of house appears to have been applied in the 17th century, but seems to have been introduced in the period of peace and prosperity after the relief of Leiden in 1574. The type has a characteristic design and plan. The plan consists of a deep front part of the house with a separate rear part of the house or a rear extension. The plan has a specific layout and particularly on the ground floor a logical use of space is to be seen, related to daylight access. The major rooms face the external wails with the bedrooms and vertical transport in between. The functions on the ground floor are a shop/workshop facing the street with a heated dayroom with box bed belonging to the shop/workshop. The rear extension or the separate rear part of the house has a kitchen function. The layout of the floor (if existing) contains two heated living rooms, also with box beds in the middle zone. The ground floor probably functioned as a business zone and the floor as a living zone, when the business was closed. As the houses lack a large storage capacity, trades were practiced, for instance related to the textile industry, for which such capacity was not required. The structural principles are brick walls, with joint walls as side elevations. The floors show the transition from the generally older floor construction with composite wooden joisting to the more modern floor with simple joisting. Both principles occur, in the first as well as in the later town extensions (1611 and 1644/1658). A composite joisting was preferred, at any rate for the representative rooms. For the construction of the roof trusses with triangle trusses on top of them were usually applied. The wooden vice in a brick stairwell is part of the construction. This type of house was frequently built from the end of the 16th century, having its peak in the 17th-century town extensions. It was such a practical type that in the 19th century new versions were still built.